Mesenchymal Stem Cells in Premature Ovarian Insufficiency: Mechanisms and Prospects - Li, Zhongkang; Zhang, Mingle; Tian, Yanpeng; Li, Qian; Huang, Xianghua (Frontiers in Cell and Developmental Biology, 2021)
Premature ovarian insufficiency (POI) is a complex endocrine disease that severely affects the physiological and reproductive functions of females. The current conventional clinical treatment methods for POI are characterized by several side effects, and most do not effectively restore the physiological functions of the ovaries. Transplantation of mesenchymal stem cells (MSCs) is a promising regenerative medicine approach, which has received significant attention in the management of POI with high efficacy. Associated pre-clinical and clinical trials are also proceeding orderly. However, the therapeutic mechanisms underlying the MSCs-based treatment are complex and have not been fully elucidated. In brief, proliferation, apoptosis, immunization, autophagy, oxidative stress, and fibrosis of ovarian cells are modulated through paracrine effects after migration of MSCs to the injured ovary. This review summarizes therapeutic mechanisms of MSCs-based treatments in POI and explores their therapeutic potential in clinical practice. Therefore, this review will provide a theoretical basis for further research and clinical application of MSCs in POI.